The Application of Collaborative Writing Strategy in Teaching Composition in a Public Junior High School - Suparto, Windy Puspitasari; Yusmah, Yusmah; Kasman, Nuraini; Amir, Muhammad; Wafi, Abdul (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The qualitative descriptive method was used by the researcher in this study. The term "qualitative descriptive research" refers to a survey study that determined and described the use of a collaborative writing strategy in teaching composition. The study's objectives are to learn how the teacher uses the collaborative writing strategy in teaching composition in a public junior high school, as well as the students' reactions to the strategies used by the teacher in teaching writing in a public junior high school. The teachers and students of UPT SMP Negeri 6 Makassar's ninth grade were the study's subjects. As a result, the researcher chose one of the two teachers at this school who could use Microsoft 365 and two classes, BI.2 and 9. A, as the subjects of the study. According to the findings, the English teacher at UPT SMP Negeri 6 Makassar frequently employs three of five strategies, including horizontal division parallel writing, stratified division parallel writing, and reactive writing strategy. Furthermore, the researcher discovered that students' responses to the strategies that the teacher implemented in teaching writing of collaborative writing gave a positive response toward the collaborative writing strategy that the teacher used, and students' responses to the strategies that the teacher implemented in teaching writing tend to prefer groups in the form of group discussions rather than writing alone because they cannot exchange information and understanding. Because the students' background knowledge is still insufficient, the researcher discovered that group single author writing and sequential single writing are rarely used by the teacher during the research process.